IDENTIFIKASI KELAYAKAN USAHA BUMDES PADA ASPEK SOSIAL DAN EKONOMI (Studi Kasus BUMDes Mekar Sari Mandiri Desa Mekar Sari Kabupaten Kepahiang) - Hartini, Kustin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
Village economy is one of the important factors in assessing the success of village development the Law No. 6 of 2014 concerning Village Article 1 paragraph 6 stipulates that Village-Owned Enterprises, hereinafter referred to as BUMDes, are business entities whose whole or part of their capital is owned by the Village through direct participation originating from Village assets separated to manage assets, services services and other businesses for the greatest welfare of the village community. This confirms that the management of BUMDes is fully implemented by the Village community, from the Village, by the Village and for the Village in an effort to strengthen the village economy and is formed based on the needs and potential of the VillageThe establishment of the BUMDes is expected not only to be oriented towards the profit of the institution but also to prioritize the benefits for improving the economy and welfare of the village community. This study aims to conduct a feasibility assessment of the implementation of business activities of Village-Owned Enterprises (BUMDes). This research was conducted with descriptive qualitative methods with data collection techniques in the field using interview methods, documentation, observation and literature review with the research subjects being village officials, BUMDes managers and communities using BUMDes services. Measurement assessment analysis uses indicators of feasibility study aspects. The results showed that the existence of BUMDes was in accordance with the objective of establishing BUMDes in an effort to improve the economy of the village community, that BUMDes Mekar Sari Mandiri in Mekar Sari Village, Kepahiang Regency from the results of business feasibility assessment especially on social and economic aspects had a positive and direct impact. for local village governments and especially communities around BUMDes